Strategi Penyuluh Agama Islam dalam Menangani Dampak Pernikahan Dini Pada Remaja di Kabupaten Pekalongan - Lintang Kusuma, Regina Wahyu; Rifa'i Subhi, Muhamad (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2024)
Abstract: The purpose of writing this article is to identify the strategies of religious counselors in dealing with the impact of early marriage on teenagers. The method used is qualitative library and also interviews, interviewing a number of religious figures as primary data and conducting library studies such as sources from journals or previous research as secondary data, data obtained from interviews and library studies with a focus on strategies of Islamic religious instructors in overcoming The impact of early marriage on teenagers. The phenomenon paradigm is applied to explore the situation in Pekalongan Regency. The results of this research are the strategies of religious counselors in dealing with the impact of early marriage on teenagers. The results of the research above show that the strategy of Islamic religious counselors in dealing with the impact of early marriage on teenagers emphasizes a holistic and collaborative approach, involving the government, religious leaders and the community. Islamic religious extension is recognized as a strategic key, with local cooperation and adaptation of outreach programs according to culture.Abstrak: Tujuan penulisan artikel ini adalah untuk mengidentifikasi bagaimana strategi penyuluh agama dalam menangani dampak pernikahan dini pada remaja. Metode yang dilakukan adalah kualitatif library dan juga wawancara, mewawancari sejumlah tokoh agama sebagai data primer dan melakukan studi library seperti sumber dari jurnal atau penelitian terdahulu sebagai data sekunder, data yang diperoleh dari hasil wawancara dan studi library dengan fokus pada strategi penyuluh agama Islam dalam mengatasi dampak pernikahan dini pada remaja. Paradigma fenomena diterapkan untuk mengeksplorasi situasi di Kabupaten Pekalongan. Hasil penelitian ini bagaimana strategi penyuluh agama dalam menangani dampak pernikahan dini pada remaja. Hasil penelitian di atas menunjukkan bahwa strategi penyuluh agama islam dalam menangani dampak pernikahan dini pada remaja lebih menekankan pendekatan holistik dan kolaboratif, melibatkan pemerintah, tokoh agama, dan masyarakat. Penyuluhan agama Islam diakui sebagai kunci strategis, dengan kerjasama lokal dan adaptasi program penyuluhan sesuai budaya.